2021
DOI: 10.1108/sef-08-2020-0342
|View full text |Cite
|
Sign up to set email alerts
|

Systemic risk contagion within US states

Abstract: Purpose This study aims to examine the systemic risk contagion in banks from 15 US states using extreme shocks in their distance to risk. Design/methodology/approach The authors contemplate a model that inputs co-exceedances in the base US states’ banking sector as the dependent variable and the co-exceedances in other states’ banking sector (along with other underlying variables of a banking system) as the explanatory variables. Findings The authors find smaller states transmit and receive more systemic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…They found that high-stress periods such as the COVID-19 pandemic spur an increase in contagion. This finding connects with Choudhury and Daly’s (2021) idea that larger (financial) shocks are more contagious than smaller ones. This finding means that a systemic effect is more likely in this case and with the results from Batten et al (2021).…”
Section: Literature Reviewsupporting
confidence: 85%
“…They found that high-stress periods such as the COVID-19 pandemic spur an increase in contagion. This finding connects with Choudhury and Daly’s (2021) idea that larger (financial) shocks are more contagious than smaller ones. This finding means that a systemic effect is more likely in this case and with the results from Batten et al (2021).…”
Section: Literature Reviewsupporting
confidence: 85%
“…Future researchers may extend this study by considering the calendar effects in Bitcoin’s conditional volatility that significantly affect its return (Kinateder and Papavassiliou, 2021). Another area of interest might be the contagion risk to other developed or even developing countries (Choudhury and Daly, 2021; Choudhury et al , 2021; Daly et al , 2019; Yoon et al , 2021) as the financial risk during COVID-19 in the Australian stock markets may trigger spillover effects.…”
Section: Discussionmentioning
confidence: 99%
“…A strong and resilient banking system is the foundation for sustainable economic growth, as banks are the hubs for credit intermediation and a well-acknowledged connection for service activities [51]. The results presented in this study suggest that the banking system is exposed to significant domestic contagion risks arising from systemic defaults supported by other authors in the field [52]. This is because the Chinese markets provide weak signals of forthcoming stress in banking systems.…”
Section: Discussionmentioning
confidence: 57%